Quick Access to 2,2’-Bipyridines from Halopyridines and Pyridines Using Transition Metals: A Short Review - Kumar, N.S.; Adhikary, A. (Letters in Organic Chemistry, 2025)
Over the past decades, 2,2’-bipyridines and their derivatives have significantly contributed to the field of advanced materials, synthesis, and catalysis. In particular, the structural ability of bipyridines to accommodate numerous types of functional groups with varying electronic and steric properties resulted in their diverse applications. In this regard, developing novel and cost-effective preparative methodologies for 2,2’-bipyridines having various substituents has always been a popular area of research. Starting from pyridine derivatives, the simplest route to these molecules includes homo-, hetero-, and cross-coupling reactions. This review concentrated on transition metal-mediated one-step procedures for 2,2’-bipyridines from inexpensive and abundant starting materials, specifically, pyridines and 2-halopyridines. Although this report focuses on self-coupling techniques, convenient hetero-coupling methods are included. Special attention is given to the substrate scope details of the existing methodologies.
Keywords: transition metal catalysis